Research status and prospects of exosomes in the treatment of intervertebral disc degeneration - Feihong HUANG; Hua JIANG (Guangxi Yike Daxue xuebao)
Intervertebral disc degeneration (IDD) is characterized pathologically by a reduction in nucleus pulposus cells, inflammation of the cartilaginous endplate, and annulus fibrosus rupture. Regenerative therapies aimed at restoring the normal physiological structure of the intervertebral disc have been a focus of research, with exosome (Exo) therapy receiving considerable attention in recent years. Many studies have shown that Exos exert therapeutic effects on IDD by maintaining extracellular matrix homeostasis, inhibiting cell apoptosis, and exhibiting antioxidant and anti-inflammatory properties, thereby restoring the structural and functional characteristics of degenerated intervertebral discs. This review summarizes the current research status of Exos from different cellular sources in the field of IDD treatment, analyzes the advantages and disadvantages of Exos compared to various biological therapies, and discusses the future prospects of Exo therapy.